The Application of Character Education in the Holistic Personality Development of Students at MAN 2 Bekasi - Sa’diah, Titin; Zumailah, Elly; Junaedi, Dedi; Fathuloh, Fathuloh; Arifin, Bambang Syamsu (TARBAWY: Indonesian Journal of Islamic Education, 2023)
The aim of this research is to gain an understanding of how character education can be applied to develop students' broader personalities. The method used uses a qualitative approach. The research was conducted at MAN 2 Bekasi. The principal, deputy principal, homeroom teacher, teachers and students were important sources interviewed. Data were analyzed using the following steps: data collection, data analysis, and conclusion/verification. The research results are as follows: (a) management of character education can be carried out internally and externally in schools; (b) internal school strategies can be implemented: teaching and learning in the classroom, daily activities within the school culture, and curricular and extracurricular activities; and (c) external school strategies can be implemented through the synergy of school educators, students and parents.